PLACENTAL EFFICIENCY AND MORPHOLOGY IN EWES AS INFLUENCED BY GENETIC GROUP, AGE, WEIGHT AND LITTER CHARACTERISTICS - KUMAR, ANIL; R,; IYUE, M (The Indian Journal of Animal Reproduction, 2023)
The effects of breed, age, weight of ewes, litter size, litter weight and sex of lamb on placental characteristicsand placental efficiency were studied in the present study to establish the fact that they determine the birthweight. Average placental weight was recorded as 307.66 0 14.24 g. Ewes with good body weight at breedinghad significantly heavier placenta. Twin bearing ewes, ewes with male lambs and higher litter weight had higherplacental weight. Weight of placenta had a positive correlation with length and width of placenta and also with thenumber of big and small cotyledons. Among the three genetic groups studied Dorset X Nilagiri cross bred eweshad longer placenta with bigger cotyledons and more number of cotyledons than Nilagiri and Sandyno ewes. Littersize and sex of lamb had significant effect on the placental length. Ewes with twins and ewes with male lambshad higher placental length, bigger cotyledons and more number of cotyledons. Average placental efficiency was10.7200.20 g. Litter weight at birth and placental weight had significant effect on placental efficiency and weresignificantly higher in twin bearing ewes than single lambs.
Keywords: Ovine; Placenta; Breed; Litter size; Litter weight; Placental efficiency